Decreased insulin binding to mononuclear leucocytes and erythrocytes from dogs after S-Nitroso-N-Acetypenicillamine administration - McGrowder, Donovan (BioMed Central, 2002)
BACKGROUND: Nitric oxide (NO) and oxygen free-radicals play an important part in the destruction of beta-cells in auto- immune diabetes although the precise mechanism of interaction is still not known. This study was designed to examine any possible diabetogenic effect of NO by investigating any differences in cellular binding of insulin to its receptor on the cell membranes of erythrocytes and mononuclear leucocytes of dogs treated with the NO donor, S-nitroso-N-acetylpenicillamine (SNAP) and controls treated with captopril. RESULTS: The result obtained showed decreased binding of insulin to its receptor on the cell membranes of erythrocytes and mononuclear leucocytes. Mononuclear leucocytes from SNAP-treated dogs had decreased ability to bind insulin (16.30 ± 1.24 %) when compared to mononuclear leucocytes from captopril-treated controls (20.30 ± 1.93 %). Similar results were obtained for erythrocytes from dogs treated with SNAP (27.20 ± 1.33 %) compared with dogs treated with captopril (34.70 ± 3.58 %). Scatchard analysis demonstrated that this decrease in insulin binding was accounted for by a decrease in insulin receptor sites per cell, with mononuclear leucocytes of SNAP-treated dogs having 55 % less insulin receptor sites per cell compared with those of captopril-treated controls (P < 0.05). Average affinity and kinetic analysis revealed a 35 % decrease in the average receptor affinity, with mononuclear leucocytes from captopril-treated controls having an empty site affinity of 12.36 ± 1.12 × 10(-8) M(-1) compared with 9.64 ± 0.11 × 10(-8) M(-1) in SNAP-treated dogs (P < 0.05). CONCLUSION: These results suggest that acute alteration of the insulin receptor on the membranes of mononuclear leucocytes and erythrocytes occurred in dogs treated with S-nitroso-N-acetylpenicillamine. These findings suggest the first evidence of the novel role of NO as a modulator of insulin binding and the involvement of NO in the aetiology of diabetes mellitus.